Case Report: The case of atypical OAPS complicated by positive anti-SSA and anti-SSB antibodies - Huang, Chunyan; Hong, Daorong; Chen, Xiaoqing (Frontiers in Immunology, 2025)
Antiphospholipid syndrome (APS) is a systemic autoimmune disease. When pathological pregnancy manifestations—such as recurrent miscarriage, stillbirth, preeclampsia, and preterm birth—predominate, the condition is called obstetric APS (OAPS). OAPS can be typical or atypical. Pregnant women positive for anti-Ro/SSA and SSB antibodies may develop fetal congenital heart block (CHB). Meanwhile, antiphospholipid antibodies (aPL) can cause preeclampsia, fetal growth restriction, intrauterine fetal death, and other adverse outcomes through mechanisms including disruption of trophoblast function. Here, we describe a case of atypical OAPS complicated with anti-Ro/SSA and SSB antibody positivity during pregnancy, who developed a subchorionic hematoma. At presentation, the hematoma was progressively enlarging, yet the patient had only one moderate-to-high titer of anti-β2-GP1 antibody and a transient low titer of ACL-IgM, not meeting clinical or laboratory criteria for OAPS. Delaying diagnosis and treatment to wait for repeat aPL testing after 12 weeks would increase risk of poor outcomes. Facing overtreatment and undertreatment challenges, we chose high-dose corticosteroids, hydroxychloroquine, and intravenous immunoglobulin therapy. When the hematoma shrank, low-molecular-weight heparin (LMWH) and aspirin were added with close monitoring, and after two weeks, both the hematoma and placental blood sinuses resolved. During pregnancy follow-up, multiple anti-β2-GP1 antibody tests showed moderate-to-high titers (over 12 weeks apart), confirming our diagnosis. Besides these immunological abnormalities, the patient was also positive for anti-SSA and anti-SSB antibodies and had a prior pregnancy complicated by suspected fetal ventricular septal defect, a high-risk factor. In light of this risk, the patient was treated with hydroxychloroquine. As a preventive strategy, two courses of intravenous immunoglobulin (IVIG) were also initiated at 16 weeks of gestation to support maternal-fetal immune tolerance. After treatment, no fetal cardiac abnormalities were observed, and a healthy female infant was vaginally delivered at 38 + 4 weeks. Diagnosing such cases and correct timing and choice of medication are critical for women of childbearing age. Most women with immune-related antibody positivity can achieve successful pregnancy and delivery with appropriate treatment.